Environmental requirements for optimal naval operational efficiency - Uys, R L (Department of Oceanography, 2016)
In this thesis the applicability of ocean environment modelling as a part of optimal naval operational efficiency, and thus military oceanography, is evaluated. To be able to do this, the principles of knowledge-based warfare and the ability to make rapid environmental assessments, are introduced. These then form part of optimal efficiency. Modelling of the environment implies knowledge-based warfare and accommodates the ability to make a rapid environmental assessment. After an overview of past and current ocean modelling (specifically wave modelling), the third generation SWAN (Simulating WAves Nearshore) model is selected to model a small component of the military oceanographic spectrum viz. waves. The selected area, includes an area where the US Navy conducted an amphibious landing exercise (Operation Laurel) during October 2001. Three case studies are considered for modelling. These included an extreme wave condition, a mode wave condition and the conditions during Operation Laurel. Data were obtained from the wave rider buoy at Slangkop near Cape Town and analysed for a specific period during 2001. In all three cases the wave dissipation and maximum energy transfer areas were determined from the model. From these, certain deductions could be made regarding the influence the environment under these three different conditions could have on naval operations in the littorals. It is concluded that ocean modelling should form an integral part of naval operational efficiency and its contribution as force multiplier should be taken into consideration.